(untitled) (Linguostylistic Studies, 2017)
The article highlights the issue of the conceptualization of the biblical lexeme «cross» in the Ukrainian phraseologisms of the colloquial origin, laying emphasis on the identification of the nucleus and the periphery of the semantic actualization of this lexeme. It has been revealed that the nuclear zone of the concept «cross» in the Ukrainian colloquial phraseologisms is realized on the basis of perceiving the concept «cross» as a sacred symbol of the Christian religion. This realization manifests itself in several dimensions: the highest sacred value, a means of punishment, means/matter of ethical opposition, etc. The immediate periphery of the concept «cross» – perception of it as a symbol of suffering or spiritual weapon – is also directly related to the sacred content of the lexeme. Semes of a corresponding geometric figure or a sign, the Order of Merits is actualized in the lexeme «cross» as a more distant periphery. The article contains the scheme, designed by the author, which represents the structure of the concept «cross» in the Ukrainian phraseological units of the spoken colloquial origin.